ECDIS-GNSS Combined to Improve Marine Traffic Safety - Pira, Rosario La (The International Hydrographic Review, 2010)
This paper analyses the enhanced GNSS and ECDIS technology in the realm of maritime navigation from the user’s perspective taking into account the latest changes in international regulations and standards. It is through this integration that mariners have the possibility to analyze their own ship’s position related to the chart information for a safer decision-making process and where the best accuracy of the position data can be properly managed. To obtain the maximum advantage of this enhanced technology a different approach by the mariner is required and a specific training program that provides comprehensive instruction on safe equipment operation must be developed.